Implementasi Metode SSADM pada Perancangan Sistem Informasi Layanan Administrasi Sekolah Berbasis Web di Dinas Pendidikan dan Kebudayaan Kabupaten Situbondo - Ikrom Cemara; Adi Susanto; Wawan Tofik (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Department of Education and Culture of Situbondo Regency is a government agency responsible for providing administrative services to schools within its jurisdiction. However, based on field survey results, the current system still faces significant challenges due to its lack of integration. For instance, the process of collecting physical documents and tracking application status remains inefficient, leading to various obstacles such as service delays, risks of data loss, inconvenience for applicants, and limited transparency and accountability in data management. To address these issues, this study proposes the design of a web-based school administrative service information system. The system development process employs the Structured Systems Analysis and Design Method (SSADM), which emphasizes systematic and structured procedures to ensure functionality and efficiency. The results of this study highlight the importance of adopting information technology within government institutions, particularly the Department of Education and Culture of Situbondo Regency, as a means of supporting administrative activities. The proposed web-based system is expected to streamline administrative processes, improve service delivery, and enhance transparency in managing school-related data. Moreover, by integrating digital solutions into governance, the system can contribute to strengthening the quality of education management and supporting better decision-making processes. Ultimately, the design of this information system demonstrates the potential of technology to transform public sector services and foster accountability in education governance.